Vertebrate fauna of the Toruń Valley - Przystalski, Andrzej; Brauze, Tomasz; Kasprzyk, Krzysztof (Ecological Questions, 2010)
Being a mosaic of miscellaneous habitats, the Toruń Valley is a refuge for numerous species of animals, who find their shelter here, food and favourable places for reproduction. Countrywide, the Valley is also an important natural ecological corridor for those animals. Regarding this function, the Vistula River is of particular significance within the described area. This study presents species of wild animals from all taxonomic groups of vertebrates, which occur in the Toruń Valley. Apart from the list and the total number of species in individual taxa of higher rank, short descriptions of habitat requirements were provided together with the information on changes in the population resources of some major species. More attention was devoted to species, which withdrew from this area, as well as to those which were subject to the process of restoration. More space in the text was also dedicated to those species of vertebrates, which occur in frequent mosaics of heaths, psammophilous grasslands and encroaching pine forests. In the paper, the attention was also directed to threats posed to fauna by a hydrotechnical investment undertaken on the Vistula River upstream from the city of Toruń, as well as to the significance of Natura 2000 areas legislated in the Toruń Valley for the protection of species and habitats.